2005
DOI: 10.1038/sj.bmt.1705020
|View full text |Cite
|
Sign up to set email alerts
|

Solid tumors after hematopoietic stem cell transplantation in Japan: incidence, risk factors and prognosis

Abstract: Summary:To evaluate the incidence, risk factors and prognosis for solid tumors after hematopoietic stem cell transplantation (HSCT) in Japan, 809 patients who had received HSCT between 1981 and 2000 were retrospectively analyzed. In all, 19 newly diagnosed secondary cancers were observed. The risk for cancer development was 2.8 times as high as that for expected cases. The cumulative incidence ratios at 5 and 10 years were 1.9 and 4.2%, respectively. The risk was significantly elevated for buccal cavity cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 34 publications
3
46
4
Order By: Relevance
“…These results are similar to those reported previously. Curtis et al 4 reported the cumulative incidence of secondary solid cancer as 2.2 and 6.7% at 10 and 15 years, respectively (RR 2.7 compared with the general population) in 19 229 allografts; this was the largest study to evaluate the incidence of secondary malignancies after allograft to 5 reported that cumulative incidence at 5 and 10 years was 1.9 and 4.2%, respectively, in 809 Japanese HSCT recipients. But, these two studies included both allogeneic and autologous transplant recipients for analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those reported previously. Curtis et al 4 reported the cumulative incidence of secondary solid cancer as 2.2 and 6.7% at 10 and 15 years, respectively (RR 2.7 compared with the general population) in 19 229 allografts; this was the largest study to evaluate the incidence of secondary malignancies after allograft to 5 reported that cumulative incidence at 5 and 10 years was 1.9 and 4.2%, respectively, in 809 Japanese HSCT recipients. But, these two studies included both allogeneic and autologous transplant recipients for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Although these studies demonstrated that the risk of developing secondary solid tumors is significantly higher in allo-HSCT recipients in Western countries, only a few data documenting the incidence for secondary solid tumors in the Japanese population are available. 5 Thus, we retrospectively analyzed 2062 Japanese allo-HSCT recipients registered to the Kanto Study Group for Cell Therapy database, in order to determine the incidence and risk factors of secondary solid tumors following allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…The reported cumulative incidence of solid cancers following allogeneic SCT ranges from, 1.2% to 1.6% at 5 years, 2.2 to 6.1% at 10 years and from 3.8 to 14.9% at 15 years post transplantation (1,2,4,(20)(21)(22)(23)(24). There is no evidence for any plateau in the incidence rate (4); rather the slope of the curve continues to show a steadily increased incidence with increased follow-up.…”
Section: Solid Tumorsmentioning
confidence: 93%
“…15 Prior large-scale non-population-based studies have examined both adult and child HCT recipients, and more importantly allogeneic and autologous HCT recipients together, making inferences about second cancer risk in adult autologous HCT recipients difficult. 4,[6][7][8]13,17 Other reports of second cancer rates after autologous HCT have not statistically compared the observed cancer rates with those of the general population. 10,11,18,19 Compared with the general population, we found an elevated second cancer risk in males, young adults and the earlier transplant eras.…”
Section: Discussionmentioning
confidence: 99%